2008
DOI: 10.1074/jbc.m803075200
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interactions of Monoubiquitylated Transactivators with the Proteasome

Abstract: Destabilization of activator-DNA complexes by the proteasomal ATPases can inhibit transcription by limiting activator interaction with DNA. Modification of the activator by monoubiquitylation protects the activator from this destabilization activity. In this study, we probe the mechanism of this protective effect of monoubiquitylation. Using novel label transfer and chemical cross-linking techniques, we show that ubiquitin contacts the ATPase complex directly, apparently via Rpn1 and Rpt1. This interaction res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…Although the exact mechanisms by which the 19 S RP participates in substrate degradation remain to be completely elucidated (64), Rpn1 and Rpn2 are known to play a major role in processing and unfolding polyubiquitin chains and in transferring ubiquitinated proteins to the 20 S core where they are degraded (7,(11)(12)(13)(14)(15). Recent studies, as well as the present experiments, demonstrated that association of the 20 S CP with Rpn2 results in enhanced 20 S activity (7).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although the exact mechanisms by which the 19 S RP participates in substrate degradation remain to be completely elucidated (64), Rpn1 and Rpn2 are known to play a major role in processing and unfolding polyubiquitin chains and in transferring ubiquitinated proteins to the 20 S core where they are degraded (7,(11)(12)(13)(14)(15). Recent studies, as well as the present experiments, demonstrated that association of the 20 S CP with Rpn2 results in enhanced 20 S activity (7).…”
Section: Discussionmentioning
confidence: 71%
“…The 19 S RP consists of a lid and base subcomplex, with the base subcomplex, including the nonenzymatic Rpn1 and Rpn2 toroids, surrounded by six AAA-type ATPases. Rpn1 and Rpn2 appear to play a major regulatory role by modulating the translocation and subsequent degradation of ubiquitinated substrates in the proteolytic core of the 20 S CP (7,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed mechanism by which ubiquitylation protects Gal4 from the APIS complex has been worked out recently (17).…”
Section: Discussionmentioning
confidence: 99%
“…This activity requires direct interactions between the APIS complex and the activation domain of the Gal4 protein (15). APIS-mediated disruption of Gal4⅐DNA complexes occurs only when Gal4 is not mono-ubiquitylated within the DNA-binding domain (15,17) revealing at least one function of this posttranslational modification (18) to be protection against the destabilizing activity of the proteasomal ATPases. This protective effect involves direct interaction of the mono-ubiquitin moieties with Rpn1 and Rpt1 in the APIS complex, an interaction that disrupts the binding of Rpt4 and Rpt6 to the activation domains of the Gal4 dimer, thus preventing the APIS complex from using the activator as a substrate for its unwinding activity (17).…”
mentioning
confidence: 99%